Perencanaan Purwokerto Technology Park Dengan Konsep Arsitektur Kontemporer - WIDYANDINI, WITA; UMAROH, JIHAN MUFIDAH; BASUKI, (ReTII, 2021)
Science and technology are the determining factors for a country to be able to move forward to save the economy. In Indonesia the development of science and technology parks (STP) has been encouraged by the Government since 2002. which is regulated in Law Number 18 of 2002. The planning of Purwokerto Technology Park as a bridge to connect government and educational institutions in the field of information technology with the industrial world. The rapid development of the city of Purwokerto has great potential for the fulfillment of technology education facilities and business activities. The research methodology used is the qualitative method, with observation, interview, and dokumentation as the data collection technique, so that the data collected is in the form of words, pictures, and not numbers.The research results are 1) The basic form of Purwokerto Technology Park is a hexagonal shape, 2) The application of contemporary architecture are transparent materials, monochrome color, building voids, and the application of kinetic facade.